Distinguishing ventricular septal bulge versus hypertrophic cardiomyopathy in the elderly. Issue 14 (27th April 2016) - Canepa, Marco; Pozios, Iraklis; Vianello, Pier Filippo; Ameri, Pietro; Brunelli, Claudio; Ferrucci, Luigi; Abraham, Theodore P
Abstract : The burgeoning evidence of patients diagnosed with sigmoidal hypertrophic cardiomyopathy (HCM) later in life has revived the quest for distinctive features that may help discriminate it from more benign forms of isolated septal hypertrophy often labelled ventricular septal bulge (VSB). HCM is diagnosed less frequently than VSB at older ages, with a reversed female predominance. Most patients diagnosed with HCM at older ages suffer from hypertension, similar to those with VSB. A positive family history of HCM and/or sudden cardiac death and the presence of exertional symptoms usually support HCM, though they are less likely in older patients with HCM, and poorly investigated in individuals with VSB. A more severe hypertrophy and the presence of left ventricular outflow obstruction are considered diagnostic of HCM, though stress echocardiography has not been consistently used in VSB. Mitral annulus calcification is very prevalent in both conditions, whereas a restrictive filling pattern is found in a minority of older patients with HCM. Genetic testing has low applicability in this differential diagnosis at the current time, given that a causative mutation is found in less than 10% of elderly patients with suspected HCM. Emerging imaging modalities that allow non-invasive detection of myocardial fibrosis and disarray may help, but have not been fully investigated. Nonetheless, there remains a considerable morphological overlap between the two conditions. Comprehensive studies, particularly imaging based, are warranted to offer a more evidence-based approach to elderly patients with focal septal thickening.